The Implication of Denpasar Mayor Regulation Number 36 of 2018 Concerning the Reduction of the Use of Plastic Bags on the Investment Climate in the Tourism Industry Sector in Denpasar City - Ni Ketut Sari Ardani; I Ketut Widia; I Wayan Rideng (Community Service Journal of Law, 2022)
Tourism is a very complex and mass industry, involving many people from all walks of life and professions. Tourism as the foundation of many people's lives is very vulnerable to issues, especially the issue of cleanliness and environmental pollution. Plastic waste, one example of which is the disposal of plastic containers by the community has become a global issue that can disrupt the large-scale tourism industry. The piles of rubbish that mount in every refuse disposal site or landfill, are truly heartbreaking, embarrassing, and very disturbing to the beauty and comfort of the community. That's why the community and the Government of the City of Denpasar took the initiative to save Denpasar City Region in the hope of having an impact on the preservation of the global environment. This journal intends to identify the problem that is the obstacle to the implementation of Denpasar Mayor Regulation Number 36 Year 2018 concerning the Reduction of the Use of Plastic Bags on the investment climate in the tourism industry sector in Denpasar City. The second problem is how the Implementation of Denpasar Mayor Regulation No. 36 of 2018 impacts the investment climate in the tourism industry sector in Denpasar City. The theories used in this study are Legal System theory, Investment Theory and Tourism Theory. The type of research used in this study is the legal research. In this research, the legal research is conducted by giving the education for the community and giving a law enforcement. The conclusion from this research is that the obstacle to the implementation of Denpasar Mayor Regulation No. 36 of 2018 is that the level of understanding and awareness of the legal community need to be improved. While the implication of Denpasar Mayor Regulation No. 36 of 2018 on the tourism industry is very significant, more and more tourists will visit Denpasar city if the environment is free of plastic waste, and it looks clean, beautiful, and pristine.